Dampak Pandemi Novel-Corona Virus Disiase (Covid-19) Terhadap Psikologi Dan Pendidikan Serta Kebijakan Pemerintah - Nurkholis Nurkholis (Jurnal PGSD, 2020)
The disease caused by Corona Virus Novel 2019 (NCov 19) is an infectious disease caused by SARS-COV-2, a type of corona virus where this disease has become a pandemic in 2019-2020. The infection spreads from one person to another through splashes (droplets) from the respiratory tract that often result when coughing or sneezing.The spread of COVID-19 which is increasingly widespread in various regions of the world, the surge in positive cases of corona not only has an impact on the economic world, but is also accepted by the education world. School closure is a response to the COVID-19 pandemic which increased access to education, more than 370 million children and adolescents did not learn because it temporarily closed or was not included in Indonesia as a step to improve the COVID-19 transfer chain.Corona outbreaks have a psychological impact, that is students who have to postpone their learning process are very helpful for trauma which makes them demotivated in learning. Making it less effective. However, students can be directed to the potential they have and are not intended for a variety of tasks to be moved which makes it able to produce learning activities Keywords: Novel Corona Virus (Ncov-19), Psychology Education, Impact of COVID-19